Apostle to the wilderness: Bishop John Medley and the evolution of the Anglican Church - Craig, Barry L. (Fairleigh Dickinson Univ. Press, 2005)
Medley's life : the early years -- John Fredericton : missionary to the wilderness -- Medley's intellectual context -- Medley the ecclesiologist -- The sacraments and ritualism -- Authority and church government